CSC786: Web Technology and Engineering / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2017)
Web applications are complex systems that provide an excess of functionality to a large number of users. They also reveal unique behaviors and demands in terms of performance, scalability, usability, and security. This course looks into Web technologies and Web engineering in the development of Web applications that collect, organize and expose information resources. This information includes markup languages, programming interfaces and languages, and standards for document identification and display. Web technologies are those related to the interface between Web servers and their clients involved in the Web application development, whereas, Web engineering is the application of systematic, disciplined and quantifiable approaches to development, operation, and maintenance of Web applications. The course also addresses the concepts, methods, technologies, and techniques of Web application.